Study of “Kutadgu bilig (Wisdom of royal glory)” abroad - Abdullaev Khamro Dauletbaevich (International Journal on Integrated Education, 2021)
This article is devoted to the issue of studying in Europe and Russia the epic “Kutadgu bilig” by Has Hacib Yusuf , which is considered significant in the Turkic-speaking peoples. In particular, is given a certain system of scientific research of Turkic and Russian turkologists